2005
DOI: 10.1016/j.atmosenv.2005.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic mercury emissions in China

Abstract: An inventory of mercury emissions from anthropogenic activities in China is compiled for the year 1999 from official statistical data. We estimate that China's emissions were 536 (7236) t of total mercury. This value includes open biomass burning, but does not include natural sources or re-emission of previously deposited mercury. Approximately 45% of the Hg comes from non-ferrous metals smelting, 38% from coal combustion, and 17% from miscellaneous activities, of which battery and fluorescent lamp production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
459
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 614 publications
(487 citation statements)
references
References 44 publications
17
459
11
Order By: Relevance
“…In China, Hg is well recovered in large-scale mining processes that use amalgamation, with an emission factor of ~0.79-g Hg/g Au production. However, Hg is poorly recovered in the small-scale (artisanal) mining process, and the emission factor is ~15-g Hg/g Au production (9). In 1999, only ~20 t of Au was produced from large-scale mining processes, and ~16 t of Hg emissions resulted (9).…”
Section: Hg and Au Miningmentioning
confidence: 99%
See 2 more Smart Citations
“…In China, Hg is well recovered in large-scale mining processes that use amalgamation, with an emission factor of ~0.79-g Hg/g Au production. However, Hg is poorly recovered in the small-scale (artisanal) mining process, and the emission factor is ~15-g Hg/g Au production (9). In 1999, only ~20 t of Au was produced from large-scale mining processes, and ~16 t of Hg emissions resulted (9).…”
Section: Hg and Au Miningmentioning
confidence: 99%
“…However, Hg is poorly recovered in the small-scale (artisanal) mining process, and the emission factor is ~15-g Hg/g Au production (9). In 1999, only ~20 t of Au was produced from large-scale mining processes, and ~16 t of Hg emissions resulted (9). Although artisanal Au-mining activities have been officially prohibited since 1996, a few illegal workshops still operate in remote areas.…”
Section: Hg and Au Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…Its annual Hg emission reached 604.7 t in 2000, accounting for 28% of the global emissions (Pacyna et al, 2006). Coal combustion and non-ferrous metal smelting are the most important anthropogenic sources (Streets et al, 2005). The large Hg emissions have resulted in serious environmental Hg pollution in China (Feng, 2004;Jiang et al, 2006;Zhang and Wong, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Average soil and root Hg levels for the current study were both near the minimum levels measured in Guizhou Province, which may be explained by lower atmospheric Hg emissions in Beijing. Streets et al (2005) reported the 1999 annual anthropogenic Hg emissions for each province in China. Higher total Hg emissions were recorded for Guizhou Province compared to Beijing (Beijing ¼ 8.83 t, Guizhou ¼ 39.00 t), while the percentage of Hg 2þ deposited locally was approximately equal (Beijing: 22%, Guizhou: 24%).…”
Section: Hg Concentration In Soil and Rootsmentioning
confidence: 99%